An Unusual Cause of an Intraperitoneal Bleed: Bleeding Hepatic Artery Pseudoaneurysm Due to an Eroding Cholecystitis - Khalid Sawalha MD; Anthony Kunnumpurath MBBS; Ronald McCann MD (SAGE Publishing, 2020)
An 80-year-old male patient presented with sepsis secondary to infected central line which was placed for native aortic valve endocarditis. He also had melena and abdominal pain prior to his presentation. Abdominal computed tomography (CT) was done, which showed cholelithiasis. Esophagogastroduodenoscopy was also done with no source of bleeding identified. Later, he developed hemodynamic instability requiring aggressive fluid resuscitation and multiple packed blood cell transfusions. In view of his hemodynamic instability, a repeat abdominal CT scan showed air droplets within the gallbladder pneumobilia, ascites, diverticulosis, and a bleeding infrahepatic hematoma measuring 6 × 10 cm, which was not on his prior scan 2 days prior. A mesenteric arteriogram was performed that identified an aneurysm of the right hepatic artery with no active bleeding; therefore, it was coiled. Due to his continued clinical decompensation, he underwent an urgent open cholecystectomy, in which serosanguineous fluid, cholecystocolic fistula, and old clot related to his previous bleed were encountered. However, control of bleeding was difficult, and the patient expired. We report this case of right hepatic artery aneurysm that we believe its etiology was related to eroding cholecystitis.